Sirt3 Attenuates Oxidative Stress Damage and Rescues Cellular Senescence in Rat Bone Marrow Mesenchymal Stem Cells by Targeting Superoxide Dismutase 2 - Ma, Cao; Sun, Yanan; Pi, Chenchen; Wang, Huan; Sun, Hui; Yu, Xiao; Shi, Yingai; He, Xu (Frontiers in Cell and Developmental Biology, 2020)
Oxidative stress is one of the main causes of aging. The process of physiological aging is always accompanied by increased levels of endogenous oxidative stress. Exogenous oxidants have contributed to premature cellular senescence. As a deacetylase located in mitochondrial matrix, Sirt3 plays critical roles in mitochondrial energy metabolism, oxidative stress regulation and cellular senescence. However, it remains unknown whether Sirt3 exerts the analogous role in cellular senescence caused by two different oxidation pathways. In this study, the function of Sirt3 was investigated in age-related natural senescence and H2O2-induced premature senescence of rat bone marrow mesenchymal stem cells (MSCs). Our results showed that Sirt3 expression was significantly decreased in both senescent MSCs, which was concerned with reduced cellular reactive oxygen species (ROS) and aggravated DNA injury. Sirt3 repletion could partly reverse the senescence-associated phenotypic features in natural and premature senescent MSCs. Moreover, Sirt3 replenishment led to the reduction in the levels of cellular ROS by enhancing the expression and activity of superoxide dismutase 2 (SOD2), thus maintaining the balance of intracellular oxidation and antioxidation, and ameliorating oxidative stress damage. Altogether, Sirt3 inhibits MSC natural senescence and H2O2-induced premature senescence through alleviating ROS-induced injury and upregulating SOD2 expression and activity. Our research indicates that Sirt3 might contribute to uncovering the novel mechanisms underlying MSC senescence and provide new insights to aging and oxidative stress-related diseases.